Development and validation of food services satisfaction scale for inpatients - Bıyıklı, Ali Emrah; Bilici, Saniye (Progress in Nutrition, 2022)
Background: Quality in hospitals includes patient satisfaction which is a multidimensional concept. Food services in hospitals are the most important factors affecting the overall satisfaction of inpatients. This study aimed to develop a scale to determine the food services satisfaction of inpatients, which is an important parameter in terms of health quality standards. Methods: The content validity was developed based on the experts’ opinions (11 experts) in the development of Food Services Satisfaction Scale for Inpatients (FSSSI). The validity and reliability of FSSSI was carried out on 240 patients with a hospitalization period of at least 3 days in a medical faculty hospital and a private hospital in Konya, Turkey.  Results: The validity (content and construct validity) and reliability (scale internal consistency) of the FSSSI was analyzed and a scale consisting of 25 items and 6 subscales was obtained. While the Cronbach’s Alpha reliability coefficient was found 0.92 for the scale, the Cronbach’s Alpha reliability coefficients of the subscales were identified as 0.84 for dietician interest; 0.81 for menu quality; 0.74 for atmospheric quality; 0.71 for food quality; 0.71 for food service quality; and 0.71 for personnel service quality. The “food quality” (r = 0.85) was found to be the most correlated subscale with the total satisfaction score. Conclusions: FSSSI is recommended as a valid and reliable scale, which can easily and rapidly measure inpatient satisfaction with food services. The scale will be useful in follow-up and assessment of the quality of nutrition services, which are the most important components of patient satisfaction. Through its subscales, it is possible to identify field specific deficiencies and carry out activities for improving the service quality.